6 - Towards Better Management of Public Education in Cameroon: The Case for Decentralisation: DOI: 10.4314/ad.v29i2.22196 - Joseph A. Tamuk (Africa Development, 2022)
This paper conceptualises centralisation and decentralisation and provides evidence that the Cameroon public education system is facing imminent decentralisation. It uses available literature and the author's teaching experience to criticise the centralised education system in Cameroon, especially in resource allocation and management. The author argues that to increase the quantity and quality of education in Cameroon, there is a need to decentralise responsibility for and control of education. He presents the model proposed by government for decentralisation and proposes roles and functions for the various levels of authority in the model.